Process systems engineering for biorefineries: new research vistas - Daoutidis, Prodromos; Kelloway, Adam; Marvin, W Alex; Rangarajan, Srinivas; Torres, Ana I (Current opinion in chemical engineering, 2013)
•Review the current state in design of biorefineries.•Provide perspective on systems research challenges and opportunities.•Highlight multiple levels of decision-making required for biorefineries. Biorefineries are envisioned as complex, integrated plants capable of using biomass feedstocks to produce a broad spectrum of chemical and fuel products. Their development is favored due to ample availability of biomass resources, and policy and economic incentives. Their design and deployment requires choices on scale, location, product portfolio and technologies to be used. Biomass processing also requires new chemical transformations and process designs, and is subject to unique logistical challenges. These factors open up exciting research vistas for process systems engineering research, ranging from enterprise-level analysis to process modeling and design. This paper highlights recent progress and future research opportunities in this emerging field.